Spatial and historic variability of benthic nitrogen cycling in an anthropogenically impacted estuary - Foster, Sarah Q.; Fulweiler, Robinson W. (Frontiers in Marine Science, 2014)
Human activities have dramatically altered reactive nitrogen (N) availability in coastal ecosystems globally. Here we used a gradient of N loading found in a shallow temperate estuary (Waquoit Bay, Massachusetts, USA) to examine how key biogeochemical processes respond to environmental change over time. Using a space-for-time substitution we measured sediment oxygen uptake, dissolved inorganic nitrogen, and di-nitrogen (N2) gas fluxes from sediments collected at four stations. For two stations we compared measurements to those made at the same locations 20 years ago. Spatial variability was not directly correlated to N loading, however the results indicate significant changes in crucial ecosystem processes over time. Sediment oxygen uptake was only 46% of the historic rate and ammonium flux only 34%. The current rate of net denitrification (36 μmol N2-N m-2 h-1) was also lower than the mean historic rate (181 μmol N2-N m-2 h-1). Additionally, at one of the stations we measured a negative average N2 flux rate, indicating that the sediments may be a net source of reactive N. These changes in benthic flux rates are concurrent with a 39% decline in net ecosystem productivity determined from long-term dissolved oxygen data. Although we cannot rule out year-to-year variability we propose that the differences measured between current and historic rates may be explained in part by concurrent changes found in water temperature, precipitation, and freshwater discharge. These regional forcings have the potential to impact N inputs to the estuary, primary producer biomass, and benthic fluxes by altering the supply of organic matter to the sediments. This work highlights the dynamic nature of biogeochemical cycling in coastal ecosystems and underscores the need to better understand long-term changes.